Public Sector Employment, Rent Seeking and Economic Growth. - Gelb, A; Knight, J; Sabot, R (1991)
Surplus labor in the public sector--a characteristic of many developing countries--is viewed in this paper as the consequence of rent-seeking behavior. A theory is presented of a segmented labor market with endogenous government hiring in response to unemployment. A simple computable general equilibrium model is used to illustrate how this can give rise to dynamic social costs and to quantify them. Fiscal resources are diverted to support the unproductive "sink." The effect of surplus labor on economic growth is shown to be substantial, while the government's attempt to reduce unemployment is shown to be futile.